2019
DOI: 10.1111/bju.14570
|View full text |Cite
|
Sign up to set email alerts
|

Intratunical injection of stromal vascular fraction prevents fibrosis in a rat model of Peyronie's disease

Abstract: Objective To investigate whether local injection of autologous adipose stromal vascular fraction (SVF) can prevent the development of fibrosis and elastosis in the tunica albuginea (TA) using a rat model of the acute phase of Peyronie's disease (PD). Methods A total of 24 male 12‐week‐old Sprague–Dawley rats were divided into three equal groups: sham; PD without treatment (transforming growth factor‐β [TGF ‐β]); and PD treated with SVF 1 day after disease induction. Sham rats received two injections of vehicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
(73 reference statements)
1
12
0
Order By: Relevance
“…In two of our previous studies, we showed that in the acute PD phase, local injection of human ADSC (hADSC) or SVF prevents the collagen III and Elastin TA accumulation [18,20]. In these studies, we injected the hADSC or autologous SVF 1 day after the TGF-β1 treatment aiming to mimic the early phase of the disease [18,20]. Our results were in line with the two preclinical studies performed by Gokce et al [36,37].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In two of our previous studies, we showed that in the acute PD phase, local injection of human ADSC (hADSC) or SVF prevents the collagen III and Elastin TA accumulation [18,20]. In these studies, we injected the hADSC or autologous SVF 1 day after the TGF-β1 treatment aiming to mimic the early phase of the disease [18,20]. Our results were in line with the two preclinical studies performed by Gokce et al [36,37].…”
Section: Discussionsupporting
confidence: 88%
“…To date, 5 preclinical studies [18,20,[35][36][37], using the TGF-β1 PD rat model, have evaluated the efficacy of locally TA ADSC injection. In two of our previous studies, we showed that in the acute PD phase, local injection of human ADSC (hADSC) or SVF prevents the collagen III and Elastin TA accumulation [18,20]. In these studies, we injected the hADSC or autologous SVF 1 day after the TGF-β1 treatment aiming to mimic the early phase of the disease [18,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 36 Few articles in the sexual medicine field have reported the use of the ARRIVE checklist. 38 , 39 , 40 , 41 This concept is very important because similar to humans, several mammals display —in aging or because of various diseases—signs of ED and alterations of important regulatory pathways of erection. 24 The lack of crucial information can prevent the correct evaluation of the final results obtained.…”
Section: General Concepts Of Translational Research—the Animal Researmentioning
confidence: 99%
“…Moreover, there was a reduction in phosphorylation and activity of Smad2, RhoA, ROCK1/2 and an upregulation of MMPs and caspases in the co-culture compared to the MFB-only set-up. Interestingly, injection of ADSCs, their lysate or stromal vascular fraction in a TGF-β1-based rat model of PD has proven to be an effective method of fibrosis alleviation in many in vivo studies (76)(77)(78)(79)(80). Even though there are some studies that have investigated the use of MSCs in PD in preclinical in vivo studies, their precise mechanism of action was not investigated, despite managing to show an antifibrotic effect on PD plaque and restoration of erectile function (76,77).…”
Section: In Vivo Studiesmentioning
confidence: 99%